Effects of Ball Milling Time on the Fire Performance Red Mud Intumescent Coating - Mohamad Lutfi, Mohamad Ashraf (IRC, 2016)
Considerable efforts have been made by several researchers worldwide to mass utilize bauxite waste (red-mud) in various applications. The examples of the red mud utilization around the world are building/construction materials such as bricks, stabilized blocks and steel coatings . In this study, the surface properties of the red mud treated by varying duration of ball milling process were investigated for their heat shielding and applicability in intumescent coating. Firstly, the red mud were treated with ball milling process to further discourage agglomeration of the particles. The red mud were subsequently mixed with other ingredients such as ammonium polyphate, boric acid, melamine and expandable graphite. The coating were applied on the steel plate and went fire and furnace test. During the fire test, the temperature of steel plate was recorded for 60 minutes at an interval of 1 minute.